أثر استخدام استراتيجية خرائط المفاهيم في مادة النحو على التحصيل الدراسي فيها - حجاج, عمر; فخار, عيسى (جامعة الوادي - University of Eloued, 2020)
تهدف الدراسة إلى معرفة أثر استخدام استراتيجية خرائط المفاهيم في تدريس مادة النحو على التحصيل الدراسي فيها، وقد استخدم البحث التصميم الثاني من التصميمات التمهيدية للمنهج التجريبي القائم على المجموعة التجريبية الواحدة مع القياس القبلي والبعدي. وتتمثل عينة الدراسة من (43 تلميذا وتلميذة) من السنة الخامسة ابتدائي يدرسون في مدرسة الشيخ محمد على دبوز - الحرة- بالقرارة ولتحقيق أهداف الدراسة ثم إعداد مادة تعليمية وفق استراتيجية خرائط المفاهيم، واختبار لقياس التحصيل القبلي، وآخر لقياس التحصيل البعدي، وقد تم حساب خصائصها السيكومترية للتأكد من صدقها وثباتها. وقد تمت الدراسة في الموسم 2018- 2019 ودامت 6 أسابيع (18 حصة). وبعد تحليل النتائج إحصائيا باستعمال برنامج توصلت الدراسة إلى النتائج التالية: 1-توجد فروق دالة إحصائيا عند مستوى 0.05 بين متوسط درجات التلاميذ في الاختبار القبلي والاختبار البعدي باختلاف طريقة التدريس لصالح الاختبار البعدي. 2- توجد فروق دالة إحصائيًا عند مستوى 0.05 في مستوى التذكر بين متوسط درجات التلاميذ في الاختبار القبلي والاختبار البعدي لصالح الاختبار البعدي. 3-لا توجد فروق دالة إحصائيًا عند مستوى 0.05 في مستوى الفهم بين متوسط درجات التلاميذ في الاختبار القبلي والاختبار البعدي. 4-لا توجد فروق دالة إحصائيًا عند مستوى 0.05 في مستوى التطبيق بين متوسط درجات التلاميذ في الاختبار القبلي والاختبار البعدي. Abstract:The study aims to determine the impact of using strategy maps concepts in teaching as on academic achievement, and has been used to search the second design of preliminary designs experimental method based on experimental group with tribal measurement walbadi. The sample of the study consisted of (43 pupils and pupil) of the fifth year of study at primary school of Sheikh Mohamed Ali Debbouze-dirt-free and achieve the objectives of the study and preparation of teaching material in accordance with strategy maps concepts, test for gauging, and another for dimensional gauging, and were calculated Psychometric characteristics to ensure its sincerity and consistency. The study took place in and lasted six weeks (18 servings). After analysing the results statistically using 9-2018the season 201 program spss19.0 the study found the following results: 1. a statistical differences at the level of 0.05 between the average scores pretest and students test post for different teaching method to fit test post. 2. There are differences statistically at 0.05 level of recollection among average pupils at pretest and post test for test post . 3.There are no statistical differences at 0.05 level of understanding between the average scores pretest and students test post. 4. There is no statistical differences at 0.05 level of application among average pupils at pretest and post test.
مقال
Keywords: استراتيجية خرائط المفاهيم - التحصيل الدراسي - تلاميذ السنة الخامسة ابتدائي; Concept maps strategy; academic achievement ; fifth year primary students.